Day 19: A Game of Inequality

Algebra Level 4

A teacher decides to play a game with her three students. She writes four positive (real) numbers on the board; a , b , c , d a,b,c,d .

One student's task is to find the sum of the cube of each number. (i.e. a 3 + b 3 + c 3 + d 3 a^3+b^3+c^3+d^3 )

Another student's task is to find the sum of the reciprocal of each number.

The final student's task is to find the sum of the squared reciprocal of each number.

When they are all finished doing this fun calculation, they multiply their answers together. What is the minimum value of their final answer?


This problem is part of the Advent Calendar 2015 .


The answer is 64.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Michael Ng
Dec 18, 2015

We have the expression: ( a 3 ) ( 1 a ) ( 1 a 2 ) (\sum a^3 )(\sum\frac1a )(\sum\frac{1}{a^2}) Now we can apply the Generalised Hölder's Inequality (for a quick outline of the proof you can consult my unfinished book in the 'A Very Useful Lemma' part').

This yields that the expression is greater than or equal to 64 \boxed{64} ; for example this occurs when all the variables are the same; which is our answer as required.

Great book! How long did it took you to write?

Pi Han Goh - 5 years, 5 months ago

Log in to reply

Thanks! It's not finished yet, but it has already taken a lots of hours to write; it has all been very interesting though!

Michael Ng - 5 years, 5 months ago
Pulkit Gupta
Dec 19, 2015

Applying AM-GM inequality to each of the three terms in the final expression ( a 3 ) ( 1 a ) ( 1 a 2 ) (\sum a^3 )(\sum\frac1a )(\sum\frac{1}{a^2}) , we obtain the minimum attainable value as 64.

The inequality is achieved when all three terms equate, or a=b=c=d=1.

James Wilson
Jan 9, 2021

Since the link to Michael Ng's book is not working, I'll post the solution he most likely has.

Applying H\"{o}lder's Inequality, in this case, with λ 1 = λ 2 = λ 3 = 1 3 \lambda_1=\lambda_2=\lambda_3=\frac{1}{3} gives

( a 3 + b 3 + c 3 + d 3 ) 1 3 ( 1 a + 1 b + 1 c + 1 d ) 1 3 ( 1 a 2 + 1 b 2 + 1 c 2 + 1 d 2 ) 1 3 (a^3+b^3+c^3+d^3)^\frac{1}{3}(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}+\frac{1}{d})^\frac{1}{3}(\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}+\frac{1}{d^2})^\frac{1}{3}

( a 3 ) 1 3 ( 1 a ) 1 3 ( 1 a 2 ) 1 3 + ( b 3 ) 1 3 ( 1 b ) 1 3 ( 1 b 2 ) 1 3 + ( c 3 ) 1 3 ( 1 c ) 1 3 ( 1 c 2 ) 1 3 + ( d 3 ) 1 3 ( 1 d ) 1 3 ( 1 d 2 ) 1 3 \leq (a^3)^\frac{1}{3}\Big(\frac{1}{a}\Big)^\frac{1}{3}\Big(\frac{1}{a^2}\Big)^\frac{1}{3}+(b^3)^\frac{1}{3}\Big(\frac{1}{b}\Big)^\frac{1}{3}\Big(\frac{1}{b^2}\Big)^\frac{1}{3}+(c^3)^\frac{1}{3}\Big(\frac{1}{c}\Big)^\frac{1}{3}\Big(\frac{1}{c^2}\Big)^\frac{1}{3}+(d^3)^\frac{1}{3}\Big(\frac{1}{d}\Big)^\frac{1}{3}\Big(\frac{1}{d^2}\Big)^\frac{1}{3}

= 1 + 1 + 1 + 1 = 4 =1+1+1+1=4

Cubing both sides of the inequality leads to the result (noting equality occurs when a = b = c = d = 1 a=b=c=d=1 ).

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...